2016
DOI: 10.1080/19420862.2016.1248012
|View full text |Cite
|
Sign up to set email alerts
|

Novel multispecific heterodimeric antibody format allowing modular assembly of variable domain fragments

Abstract: Multispecific antibody formats provide a promising platform for the development of novel therapeutic concepts that could facilitate the generation of safer, more effective pharmaceuticals. However, the production and use of such antibody-based multispecifics is often made complicated by: 1) the instability of the antibody fragments of which they consist, 2) undesired inter-subunit associations, and 3) the need to include recombinant heterodimerization domains that confer distribution-impairing bulk or enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In addition, binding affinity was not altered by VH-FR4 substitutions (cluster III), and therefore the complementarity of strand G located near A and F strands could be more thoroughly studied. Indeed, as Egan et al (2017) already showed, substitution of a human Vκ1-FR4 with the corresponding germline sequence of a λ-type VL chain improved the biophysical properties of a scFv without altering its affinity [44].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, binding affinity was not altered by VH-FR4 substitutions (cluster III), and therefore the complementarity of strand G located near A and F strands could be more thoroughly studied. Indeed, as Egan et al (2017) already showed, substitution of a human Vκ1-FR4 with the corresponding germline sequence of a λ-type VL chain improved the biophysical properties of a scFv without altering its affinity [44].…”
Section: Discussionmentioning
confidence: 91%
“…Cluster III substitutions alone had a slight negative impact whereas cluster II substitutions alone showed the best affinity profile, demonstrating improved binding (<10 −7 M) compared with scFv S1A0. One possible explanation could lie in the scFvs packing angle, in particular H47 of cluster II (or H42 in Kabat) (44). However, the predictions for cluster II show a very slight decrease of −0.1 • in the packing angle valid for the two scFvs S1C4 and S1D4 (−49.2 • ), as opposed to −49.1 • for the scFvs S1A4 and S1B4.…”
Section: Discussionmentioning
confidence: 94%
“…Bispecific antibodies, first conceptualized in 1983 (Milstein and Cuello, 1983 ), are antibodies that can bind two different antigens simultaneously. There are five fundamental groups of bispecific antibody formats: (i) asymmetric bivalent, bispecific IgG-like antibodies with heterodimeric heavy chains (HCs) (Ridgeway et al, 1996 ; Merchant et al, 1998 ; Gunasekaran et al, 2010 ; Strop et al, 2012 ; Klein et al, 2012 ; Labrijn et al, 2013 Von Kreudenstein et al, 2013 ; Brinkmann and Kontermann, 2017 ); (ii) tetravalent multispecific antibodies that are comprised of IgGs, with additional binding domains, e.g., scFvs, Fvs, VHH domains, or non-antibody binding scaffolds such as fynomers (Brack et al, 2014 ; Silacci et al, 2016 ), fused to either the N- or C-termini of either the heavy or light chains (LCs) (Coloma and Morrison, 1997 ); (iii) engineered binding domains within the normal IgG structure, such as the “two-in-one” bispecific approach from Genentech (Bostrom et al, 2009 ; Eigenbrot and Fuh, 2013 ) and the F-STAR approach of designing novel second binding sites within the C H 3 domain (Leung et al, 2015 ), (iv) engineered antibody fragments linked by short peptide linkers which can be made into bivalent, trivalent, or tetravalent formats addressing two to three targets (Mack et al, 1995 ; Holliger and Winter, 1997 ; Kipriyanov et al, 1999 ; Reusch et al, 2015 ; Egan et al, 2016 ). These may be fused to an Fc domain or other half-life extending molecule (Liu et al, 2017 ); and (v) IgGs that are chemically coupled to generate IgG-IgG conjugates (e.g., Brennan et al, 1985 ; Garrido et al, 1990 ).…”
Section: Bispecific Antibodiesmentioning
confidence: 99%
“…Additionally, the development of monotherapies targeting multiple targets can be less complex than the development of multiple drug products in combination, as well as contributing to reducing production costs. Furthermore, using multiple paratopes on multispecific antibodies can promote prolonged serum half-life, improved tissue distribution and local enrichment 87 .…”
Section: Strategic Issues In Targeting Ligandsmentioning
confidence: 99%